Re-Design of Road Geometric Planning Using Indonesian Standard Case Study: Fly Over Cakung - Hilda Puspita Aji Lestari; Indrastuti Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2023)
The construction of the Cakung flyover on a level Road is expected to solve traffic problems and ensure user comfort and safety. The construction of the Cakung flyover in East Jakarta is one of the DKI Jakarta Province Bina Marga Agency projects. This journal aims to redesign the Cakung flyover at STA PI 0+414 and STA PI 0+818 using the Bina Marga method, where there are two horizontal bends by recalculating the horizontal alignment to ensure the riders’ comfort and safety. The study results show that the Cakung flyover highway is a class IA collector Road with flat terrain with a width of 7 m, design parameters design speed (VR) of 60 km/hour and a maximum slope (e) of 8%. From the calculations, the design radius (R) is 150 and 400 m, with intersection angles of 48.587 and 24.0147. The curved horizontal length (Lc) is 87.20 and 127.65 m, and the maximum slope (e) is 8%. In this journal, the authors take the SCS (Spiral – Circle – Spiral) type of curved horizontal line that is safe for the rider according to the conditions in the field.